2015
DOI: 10.1186/s12957-016-0767-y
|View full text |Cite
|
Sign up to set email alerts
|

A clinical role of staging laparoscopy in patients with radiographically defined locally advanced pancreatic ductal adenocarcinoma

Abstract: BackgroundThe aim of current study is to verify usefulness of staging laparoscopy (stag-lap) for patient’s selection and to find prognostic factors in patients with radiographically defined locally advanced (RD-LA) pancreatic ductal adenocarcinoma (PDAC).MethodsThe LA disease was defined as an unresectable disease without distant organ metastasis based on resectability status of NCCN guideline in this study. Stag-lap was performed in 67 patients with RD-LA (2007–2012) which were divided into 4 groups according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 19 publications
0
54
0
Order By: Relevance
“…Our previous report also revealed that ascites occurred within 1-year after initiation of chemotherapy in approximately 70% of patients with peritoneal metastasis diagnosed by staging laparoscopy for radiographically defined locally advanced PDAC. 5 Considering that the patients with peritoneal metastasis generally have a particularly poor prognosis, the present survival results are encouraging.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our previous report also revealed that ascites occurred within 1-year after initiation of chemotherapy in approximately 70% of patients with peritoneal metastasis diagnosed by staging laparoscopy for radiographically defined locally advanced PDAC. 5 Considering that the patients with peritoneal metastasis generally have a particularly poor prognosis, the present survival results are encouraging.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, the presence of peritoneal metastasis is associated with development of intestinal obstruction, massive ascites, and malnutrition, leading to poor performance status, 4 which, in turn, deprives the patients of the opportunity to receive chemotherapy. 5 MST of these patients has been reported to be 6 weeks from a population-based study in the Netherlands, 3 and 7 weeks in another series of 73 patients with malignant ascites. 4 Pharmacokinetic studies revealed that anticancer drugs administered systemically do not necessarily enter the peritoneal cavity.…”
mentioning
confidence: 83%
“…Considering those reports, one option may be to administer preoperative chemotherapy for RPC patients who have high preoperative serum CA19-9 values, intending to exclude those patients who have the potential for early recurrence after surgery and to control minimally distant metastasis in those patients. It has recently been reported that staging laparoscopy in patients with local advanced pancreatic ductal adenocarcinoma is effective for selecting patients with occult distant organ metastasis [33]. To perform staging laparoscope for RPC patients having high preoperative CA19-9 values may make better patient selection for preoperative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…They reported an MST of 7 months in patients with PDAC with peritoneal dissemination, and 6 months in patients with locally advanced disease who had positive peritoneal washing cytology during staging laparoscopy. Our previous report also revealed an MST of 8 months in PDAC patients with peritoneal dissemination and 13 months in patients with locally advanced disease who had positive peritoneal washing cytology diagnosed by staging laparoscopy for radiographically defined locally advanced PDAC [5]. Moreover, we also reported that pancreas body-tail tumors and tumor size >42 mm in 110 patients with radiographicallydefined locally advanced PDAC were significantly risk factors for peritoneal metastasis [19].…”
Section: Discussionmentioning
confidence: 59%